The Dynamics of Flow Discharge and Suspension Flow Discharge in Volcano Watershed with Agroforestry Land Cover - Hadini, La Ode; Sartohadi, Junun; Setiawan, Muhammad Anggri; Mardiatno, Djati (Civil and Environmental Science Journal (CIVENSE), 2021)
The suspension flow from the upper part of a volcano watershed, which has a very thick soil condition, is sensitive to landuse form. Agroforestry is the dominant landuse form in the volcanic landscape of Indonesia. There is a lack of detailed studies about suspension flow in the upper watershed where agroforestry is the land cover. This research, performed in agroforestry area, covered the correspondence between flow discharge and suspension flow discharge, the time lag of initial rain events and the formation of suspension flow; and the characteristics of the grain size of the suspensions during the flow. The suspension flow was measured at the outlet of a gully in key watershed areas, which yielded a total of 436 suspension data. The measurement analysis was conducted at every rain event in the field and in the laboratory. The crop characteristics in the rain catchment area were recorded in details during the field survey. The characteristics of the channels converging toward the gully system were observed during the field survey. There were three relationship patterns between the peak flow discharge and the peak suspension discharge, namely (1) the peak flow discharge corresponded to the peak suspension discharge, (2) the peak flow discharge preceded the peak suspension discharge, (3) the peak flow discharge occurred after the peak suspension discharge. The average time interval between the rain events and the occurrence of suspension flow was 17.7 minutes. The peak suspension content varied from 0.0016 g/L up to 4.71 g/L with an average of 1.03 g/L. The grain size of the suspension was dominated by 71-76% of clay fraction with an average of 73% at the rising phase and 68-71% of clay fraction with an average of 69% at the falling stage.